Isolated Actinic Lichen Planus of the Lower Lip - Ellie Choi; Kong Bing Tan; Nisha Suyien Chandran (Karger Publishers, 2017)
Oral lichen planus (LP) is a common manifestation in patients with LP; however, isolated lip LP is rare and may mimic other conditions such as lichenoid drug eruptions, actinic cheilitis, and early carcinoma in situ in the absence of typical skin lesions. Actinic lichen planus (ALP) is a variant of LP occurring on light-exposed areas in patients with dark skin. We report the case of a Chinese female with isolated ALP of the lower lip, mimicking herpes simplex infection at presentation. The presence of prognathism, involvement of the lower lip, and flares associated with sunlight reinforces the role of sun exposure in the development of this condition.